Profilaktyka antymobbingowa – faktyczne działanie pracodawców czy fikcja? - Szczęsna , Iwona (Studia Edukacyjne, 2022)
Mobbing as a pathological social phenomenon destroys the values that professional work offers people and violates their dignity. Therefore, the experience of mobbing in the workplace can with out doubt be classified as a critical life event. Analysis of the mobbing situation in terms of a critical life event helps to conclude that it carries the risk of regression, destabilization in personal and professional life, and halts development if a person does not cope with the effects and consequences of the situation. That is why anti-mobbing prevention in the workplace is so important. Unfortunately, the provision of article 94 §1 of the Labor Code, regulating the employer’s obligations in the field of mobbing in the work environment, is relatively general and is limited to indicating that the employer is obliged to prevent mobbing. There is no need to look for a provision in the labor code that would specify exactly what the employer’s actions should be understood under the obligation defined in this way. The article presents the results that are part of a broader study on anti-mobbing prevention in the workplace. The narratives of the respondents were analyzed through the prism of the actual actions taken by employers in the context of anti-mobbing prevention. The research areas concerned: application of internal anti-mobbing policy, implementation of preventive training on mobbing and combating negative effects and other psychosocial risks in the workplace, and employers’ other anti-mobbing policies.